2020
DOI: 10.1007/s42729-020-00248-4
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid and Calcium Signaling Induce Physiological and Phytochemical Changes to Improve Salinity Tolerance in Red Amaranth (Amaranthus tricolor L.)

Abstract: Amaranth (Amaranthus tricolor L.) is a plant that is rich in vitamins, minerals, and phytochemicals. It is grown as a leafy vegetable in marginal environments, but high salinity levels in the soil can have a detrimental effect on its growth. These deleterious effects of salinity can be alleviated by exogenously applying signaling compounds such as salicylic acid (SA) and calcium (Ca), which can improve plant adaptation to stressful conditions. The present study evaluated the physiological and phytochemical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…2). Increased plant development promoted by SA addition was also observed in Amaranthus tricolor L. plants exposed to salinity (Hoang et al 2020). Advantages provided to plants by seed priming with SA, with emphasis on initial development processes, are attributed to a series of physiological changes caused by this compound.…”
Section: Discussionmentioning
confidence: 82%
“…2). Increased plant development promoted by SA addition was also observed in Amaranthus tricolor L. plants exposed to salinity (Hoang et al 2020). Advantages provided to plants by seed priming with SA, with emphasis on initial development processes, are attributed to a series of physiological changes caused by this compound.…”
Section: Discussionmentioning
confidence: 82%
“…SA also modulates Na transport activities. Therefore, the reduction in Na concentration with SA application (Table 2) could be due, beside K enhancement, to Ca-mediated increase in the activity of H + -ATPase, which provides the energy to remove the excessive Na from cells (Hoang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In other plant species, the gained information and outcomes remain limited as only a handful studies have been conducted in relation to salinity stress in Vietnam. Among of these studies, it has been demonstrated that exogenous application of salicylic acid and/or calcium can enhance the salinity tolerance of amaranth (Amaranthus tricolor) via promotion of Na + exclusion from roots, accumulation of phenolic and flavonoid compounds as well as increased antioxidant activities (Hoang et al, 2020). Tolerance of various chili pepper genotypes against different concentrations of NaCl or CaCl2 (ranging from 0-300 mM) has been also explored, which was based on germination rate, plant height, number of leaves, branches and flowers, leaf area, phenolic compound contents and antioxidant activities (Ai et al, 2021).…”
Section: Salinity Stress Tolerance Studies In Vietnammentioning
confidence: 99%